The income and food security impacts of soil and water conservation technologies in Tanzania - Manda, J.; Tufa, Adane H.; Alene, Arega D.; Swai, Elirehema; Muthoni, Francis K.; Hoeschle-Zeledon, Irmgard; Bekunda, Mateete A. (Frontiers Media, 2023)
Soil and water conservation technologies are critical in reducing drought and soil erosion risks and increasing crop yields and incomes. Yet, there is limited empirical evidence on the extent and impacts of adopting soil and water conservation technologies in Tanzania. The study’s objective is to evaluate the adoption (as well as the duration of adoption) and the impacts of soil and water conservation technologies on income and food security in Tanzania. The study employs a control function approach and the instrumental variable quantile treatment effects model to survey data from 575 households to estimate the average and distributional impacts of adoption. The results show that the adoption and duration of adopting soil and water conservation technologies had significant and positive effects on the total value of crop production and household income. Moreover, we find that the adoption and its duration had a significant and positive impact on the food security indicator—household dietary diversity. The results from the instrumental variable quantile treatment effects model also show that the impacts of adopting soil and water conservation technologies on the outcome variables are positive and significant, although they vary significantly across the income and food security distributions. The results indicate that even though adoption benefits households in both the lower and upper quantiles of the income and food security distributions, the marginal impacts of adoption are generally more significant for the households in the upper quantiles. The paper concludes by discussing the policy options for increasing and sustaining the adoption and impacts of soil and water conservation technologies in Tanzania.